Socio-Demographic Factors and Health-Oriented Behaviors of University Students in the Podkarpackie Region. Long-Term Prospective Research - Paweł Więch; Dariusz Bazaliński; Zdzisława Chmiel; Józef Ratajczyk; Paweł Januszewicz; Monika Binkowska-Bury (Barometr Regionalny, 2018)
The aim of the study was to achieve a prospective long-term evaluation of the impact of socio-demographic factors on students, and their healthy behaviors. It was a diagnostic survey employing a standardized interview questionnaire. The survey was conducted among 905 first-year students of medical and non-medical faculties (18–19 years of age), and the University of Rzeszów, and Rzeszów University of Technology. It was conducted in 2009 and repeated two years later. The rating of the behavior patterns of students was conducted in accordance with the following schedule: October 2009 – January 2010 (T1), October 2011 – January 2012 (T2). The level of healthy behaviors in 2012 increased significantly in a positive direction compared to 2009 (p < 0,001), in particular in the category: proper eating habits (p < 0,001) and preventive behaviors (p < 0,001). In 2009 men in the first year of the study had a lower level of healthy behaviors, an average of 3,63 points, than women (T1) and in 2012 of 5,42 points lower (T2). The level of healthy behaviors in 2012 increased significantly in a positive direction compared to 2009, in particular in the category: proper eating habits and preventive behaviors. Women showed more pro-health attitudes than men. The pro-health attitudes characterized by medical students was seen in a greater degree.